Resposta do capim tanzânia à aplicação de manganês - Sylvestre, Thiago de Barros [UNESP]; Kuhnen, Fernando [UNESP]; da Silva, Elcides Rodrigues [UNESP]; Martins, Paulo Eduardo Silva [UNESP]; de Souza Galatti, Francine [UNESP]; Prado, Renato de Mello [UNESP] (My University, 2012)
The objective was to evaluate the influence of the manganese nutritional status, growth and dry matter production of Tanzania grass. For this, we used plants of Panicum maximum Jacq. cv. Tanzânia grown in pots filled with Oxisol (Mn = 0.6 mg dm-3). The experimental design was completely randomized, with five doses of manganese (0, 15, 30, 60 and 120 mg dm-3) and four replications. The plant shoot were harvested twice, the first 42 days after sowing and the second, 30 days after the first cut. In the two sections were evaluated the number of tillers and leaves, steam diameter, plant height, shoot dry matter and in shoot-Mn concentration and root dry matter after the second cut. The application of manganese in the soil increased the levels of this nutrient in the soil and their uptake by grass, which was more than four times fold higher in the second cut compared to the first cut. The use of high rates of Mn did not affect the growth of Panicum maximum, and decreased dry matter production only for the sum of two cuts, indicating high tolerance of forage of Mn toxicity. The toxicity of Mn in forage was associated with leaf content in the first and second cut of 1,238 and 1,418 mg kg-1, respectively.
Response Tanzania grass to application of manganese
Keywords: Fertilization; Grass; Micronutrient; Panicum maximum